2020
DOI: 10.1016/j.amepre.2019.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Medicaid Expansion on Health Among Women of Reproductive Age

Abstract: Introduction: Preconception and interconception health care are critical means of identifying, managing, and treating risk factors originating prior to pregnancy that can harm fetal development and maternal health. However, many women in the U.S. lack health insurance, limiting their ability to access such care. State-level variation in Medicaid eligibility, particularly before and after the 2014 Medicaid expansions, offers a unique opportunity to test the hypothesis that increasing healthcare coverage for low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 34 publications
2
69
0
Order By: Relevance
“…Supporting this possibility, prior research suggests that treatment of diabetes increased under the ACA Medicaid expansions, [39][40][41] as did treatment of diabetes and hypertension among women of reproductive age, even as diagnosis rates for these conditions did not change. 16 These findings have direct relevance to ongoing policy discussions. We provide the first evidence that the ACA Medicaid expansions led to increased preconception health counseling, folic acid intake, and effective postpartum contraception use.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Supporting this possibility, prior research suggests that treatment of diabetes increased under the ACA Medicaid expansions, [39][40][41] as did treatment of diabetes and hypertension among women of reproductive age, even as diagnosis rates for these conditions did not change. 16 These findings have direct relevance to ongoing policy discussions. We provide the first evidence that the ACA Medicaid expansions led to increased preconception health counseling, folic acid intake, and effective postpartum contraception use.…”
Section: Discussionmentioning
confidence: 89%
“…This is consistent with prior research that found no impact of Medicaid eligibility expansions on body mass index or on diagnoses of diabetes or hypertension for women of reproductive age. 16 Our data span five years after the Medicaid expansions, but this window may be too short to expect detectable changes in the prevalence of chronic conditions or many health behaviors. Although the changes we did observe were not statistically significant, the confidence intervals on our estimates included values that could be considered clinically meaningful changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have tracked changes in Medicaid coverage and uninsurance under the law for women of reproductive age and mothers at various points relative to pregnancy. [9][10][11][12][13][14][15] Specifically, the ACA Medicaid expansion has reduced uninsurance among women of reproductive age overall, 10,11 and particular-ly among new mothers in the year after delivery. 12 Expansion has also increased preconception and postpartum Medicaid coverage.…”
mentioning
confidence: 99%